2015
DOI: 10.1002/jmri.24840
|View full text |Cite
|
Sign up to set email alerts
|

Echo time dependence of observed T1 in the human lung

Abstract: Measuring T1 at ultra-short echo times reveals a significant dependence of observed T1 on the echo time. Thus, any comparison of T1 values should also consider the TEs used. However, this dependence on TE could also be exploited to gain additional diagnostic information on the tissue compartments in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 24 publications
5
66
0
Order By: Relevance
“…We recently demonstrated that such pulses allow an echo time ‐ measured from the end of the RF‐pulse ‐ that exceeds the pulse duration . Here, we show that those pulses result in a T 1 reduction, comparable to the UTE results presented in . Also, the apparent proton density is increased when using proposed pulses.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…We recently demonstrated that such pulses allow an echo time ‐ measured from the end of the RF‐pulse ‐ that exceeds the pulse duration . Here, we show that those pulses result in a T 1 reduction, comparable to the UTE results presented in . Also, the apparent proton density is increased when using proposed pulses.…”
Section: Introductionsupporting
confidence: 85%
“…We attribute the T 1 reductions to different causes: The reduction in the muscle is most likely due to magnetization transfer caused by the increased flip angle of the SE pulse at large off‐resonance frequencies . In the vertebral bodies, a similar reduction of the apparent T 1 can be observed as shown in with a UTE sequence. Since the bone marrow consists of a fat‐water mixture, dephasing might cause different tissue to contribute differently to the signal and ultimately this might lead to different apparent relaxation times.…”
Section: Discussionmentioning
confidence: 63%
“…Since the measured baseline lung T 1 has been shown to also depend on lung blood T 1 [20]; lung blood volume changes with age and sex [21]; and lung T 1 depends on age and sex[22]; the OE-effect in the lung will likely depend on age and sex.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the pulmonary arterial compartment (deoxygenated blood) will exhibit a small decrease in R 1 with 100% oxygen breathing due to the oxygenation of hemoglobin [30,31]. Moreover, the overall blood content of the lung seems to increase with oxygen supplementation [32], and since the lung T1 is an echo time dependent mix of the lung parenchyma T1 and blood T1 [20], this mechanism will decrease the overall lung R 1 , but increase signal intensity. The observed increase in lung R 1 (global ΔR 1 on the order of 0.10 s -1 ) is explained by the large signal contribution of oxygenated blood within most voxels of the lung.…”
Section: Introductionmentioning
confidence: 99%
“…A promising technique is the direct regional quantification of T1 relaxation times. As a physical parameter, it is thought to provide an objective parameter for the characterization of pulmonary tissue independent of scanner type or observer [63]. Preliminary results obtained in patients indicate that T1 relaxation time is significantly shorter in lungs affected by emphysema or cystic fibrosis [64].…”
mentioning
confidence: 99%